Technology campuses and cities: A study on the relation between innovation and the built environment at the urban area level - Curvelo Magdaniel, Flavia Teresa de Jesús (A+BE | Architecture and the Built Environment, 2016)
This thesis examines the development of technology campuses as built environments and their role in stimulating innovation. Technology campuses entail a variety of built environments developed to accommodate technology-driven research activities of multiple organisations. The science park is the most common type of technology campus. Other types include the campuses of universities of technology and corporate R&D parks. In industrialised countries, the demand for developing technology campuses to stimulate innovation has been growing in line with the attention given to knowledge in global, national and regional policies. There are over 700 technology campuses worldwide occupying hundred thousands of hectares in- and around cities. This type of built environments have emerged and developed during critical periods of technological advancements throughout the 20th century, to support technology-based development in industrialised countries. With the adoption of the knowledge- based economy, governments in many countries have encouraged research as an essential activity in their science, technology and innovation policies. The infrastructure that supports research is also gaining momentum. The number of registered science parks is steadily increasing since the late 1990s. The number of programmes supporting research infrastructure is growing in the European policy agenda. Municipalities are formally engaged with other public and private parties in the development of urban areas targeted to stimulate innovation. Governments, universities and R&D companies are investing billions of euros in developing the infrastructure that will not only support their core processes, but will help them to remain competitive by attracting and retaining the best talent. Part of these investments are targeted to develop new buildings or entire areas that often result in campuses as we know them: a concentration of buildings accommodating organisations, people, and their activities in a (green) field. The assumption that the concentration of research activities in one location stimulates innovation is promoting the development of technology campuses in many places. However, the capacity of these built environments to support the different processes associated with innovation is not well understood – i.e. Technology campuses are urban areas in the inner city and peripheral locations that have the capacity to support the processes of knowledge creation and diffusion, as well as of attracting and retaining knowledge workers. The existent knowledge about the relationship between the built environment and innovation at the area level is limited. This knowledge gap may lead to inefficient use of the resources employed to develop technology campuses including capital, land, and time. Also, this lack of understanding can have the opposite effect, because technology campuses could easily become problematic areas dealing with vacancy, poor spatial quality, and connectivity issues frustrating the societal goal of attracting and retaining talent in the knowledge economy. A potential way to address these problems is outlining the ways in which the built environment stimulates innovation in technology campuses. In this context, this research addresses as main question ‘How does the built environment stimulate innovation in technology campuses?’ This research is grounded in the field of corporate real estate management and its theoretical assumption that the built environment is a resource managed to support the goals of organisations. Research in this field has focused on the practice of real estate management from the end user’s view. Campus development is a comprehensive form of this practice, because it deals with activities that vary from developing real estate strategies, developing building projects, up to maintaining and managing the portfolio of an organisation. The relationship between innovation and the built environment has been addressed before in theories of corporate real estate management in a broad sense. Empirically, this has been explored on the supply side at the level of the workplace rather than at the urban scale. Although the contemporary discussion of innovation in complementary research fields focus on the urban level. Onthe demand side, the involvement of public and private parties in the development of these areas moves forward the organisational scope in corporate real estate management beyond the end-users in large scale built environments. This research provides an understanding of the relationship between the built environment and innovation at the area level. This research developed knowledge clarifying such relationship in the form of a conceptual model and recommendations for practitioners involved in the practice of campus development. This knowledge developed mainly throughout an inductive approach in two core studies. The first study is an exploratory research that uncovers and positions the link between innovation and the built environment by using inputs from theory (literature review) and empirical evidence (qualitative survey of 39 technology campuses). In this stage, the link between innovation and the built environment is provided in a form of a conceptual framework containing the proposition that the built environment is a catalyst for innovation. The second study is an explanatory research that clarifies the relationship between innovation and the built environment based on empirical evidence in the practice of campus development (theory building from case studies). In this stage, the theoretical constructs of the conceptual framework are applied and revised through the in- depth study of two cases in particular contexts (i.e. High Tech Campus Eindhoven in the Netherlands and the Massachusetts Institute of technology campus in the United States). As a result, the preliminary knowledge from the exploratory research was developed into a conceptual model bearing a hypothesis and five propositions closely linked to empirical evidence. The answer to the main research question is that the built environment is a catalyst for innovation in technology campuses demonstrated by location decisions and interventions facilitating five interdependent conditions required for innovation. The following propositions explain how the built environment facilitates each of the five conditions for innovation: Location decisions and area development facilitate the long-term concentration of innovative organisations in cities and regions. Interventions enabling the transformation of the built environment at area and building levels facilitate the climate for adaptation along changing technological trajectories over time. Large-scale real estate interventions facilitate the synergy among university, industry and governments. Location decisions and interventions supporting image and accessibility define the innovation area by emphasising its distinct identity, scale and connectivity features. Real estate interventions enabling access to amenities increase the diversity of people & chances for social interaction regardless the distinct geographical settings in which the concentration of innovative activities takes place. This research acknowledges that the location decisions of some technology-driven organisations have coincidentally determined the concentration of innovative research activities in particular places. Over the years, the accommodation of the research activities of these organisations has co-evolved with particular socio-economic processes in their hosting cities creating unique conditions for innovation. The concentration of innovative organisations can be considered as a primal condition enabling the co-existence of the other four conditions for innovation. Similarly, this research acknowledges the following interventions facilitating conditions for innovation at the area level and depending on the particular location characteristics in which each campus has developed: Transforming areas through urban renewal and redevelopment, Building, adapting and re-using flexible facilities, Implementing the shared use of facilities accommodating different functions and users, Developing physical infrastructure enabling access to amenities and connection between functions Developing representative facilities and area concepts that support image. The empirical evidence supporting the propositions in the model is structured and converted into information available to decision makers involved in the development of technology campuses in the form of tools. The so-called ‘campus decision maker toolbox’ provides instruments that can guide planners, designers and managers during different stages of campus development. The tool for planners comprises campus models to frame the campus vision during the initiation of the campus based on location characteristics. The tool for designers consists of alternatives to enhance the campus brief during the preparation of the campus. And the tool for managers contains an information map to steer the campus strategy during the use of the campus. This knowledge contributes to the existing understanding of the relationship between innovation and the built environment in theory and practice. In theory, this research adds to existing theoretical concepts connecting the fields of corporate real estate management, urban studies in the knowledge- based economy and economic geography. The conceptual model proposed a new combination of existing theoretical concepts addressing a new way to look at the relationship between innovation and the built environment. In practice, this understanding is expected to encourage the efficient and effective use of the many resources required to develop technology campuses. Particularly, by providing information that can help decision makers to steer such resources towards strategic decisions and interventions that -under certain conditions- facilitate innovation. The knowledge developed in this research clarifies a relationship between innovation and the built environment at urban area level, in which the built environment facilitates conditions for innovation.